Cryogenic Freezing Equipment: a Review - S, Kumar (Journal of Postharvest Technology, 2013)
Innovative cryogenic freezing technologies can be used to produce high quality frozen foods. The potential for the development of new cryogenic equipment and processes is still enormous. This paper presents the fundamentals of cryogenic freezing and various food freezing technologies, discussing some technical descriptions of representative freezing equipment developed in the past. Product quality issues encountered when using cryogenic systems with inappropriate knowledge of the product or inadequate cold chain after cryogenic freezing -i.e. recrystallization, mechanical damage and others- are also addressed.